2016
DOI: 10.1177/8755123316675481
|View full text |Cite
|
Sign up to set email alerts
|

Music Ensemble Participation: Personality Traits and Music Experience

Abstract: ACKNOWLEDGEMENTSThere are a number of people I would like to thank who have travelled this doctoral path with me. First and foremost, I would like to thank my parents, Robert and Barbara Torrance, for their love, support, and belief in me. I would never have gotten this far in my academic career without them and the rest of my family. I will be forever grateful to my committee members, Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
4
19
0
1
Order By: Relevance
“…It seems that personality differences between different groups of musicians are small. This is also in line with studies that have suggested that in general there are no personality differences between different groups of musicians (Butkovic & Rancic Dopudj, 2017; Cribb & Gregory, 1999; Cutietta & McAllister, 1997; Langendörfer, 2008; Sandgren, 2018; Torrance & Bugos, 2017; Vaag et al, 2017; Wubbenhorst, 1994), while musicians as a group differ from the norms (e.g. Butkovic & Rancic Dopudj, 2017) or general workforce (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It seems that personality differences between different groups of musicians are small. This is also in line with studies that have suggested that in general there are no personality differences between different groups of musicians (Butkovic & Rancic Dopudj, 2017; Cribb & Gregory, 1999; Cutietta & McAllister, 1997; Langendörfer, 2008; Sandgren, 2018; Torrance & Bugos, 2017; Vaag et al, 2017; Wubbenhorst, 1994), while musicians as a group differ from the norms (e.g. Butkovic & Rancic Dopudj, 2017) or general workforce (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Woodwinds are introverted and more similar to string than brass players, while pianists are more stable (Buttsworth & Smith, 1995; Mihajlovski, 2013). Two studies examined personality differences only between singers and instrumentalists as a group (Reardon MacLellan, 2011; Torrance & Bugos, 2017), while Vaag, Sund, and Bjerkeset (2017) compared singers and seven different instrumentalist groups. In all three studies, singers were more extraverted than instrumentalists as a group or from all instrumentalist groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers have elucidated relationships between personality traits and music behaviors, instrument selection, and ensemble enrollment (Butkovic et al, 2015; Corrigall et al, 2013; Hudson, 2004; Torrance & Bugos, 2017). Although the aim of this study was not to determine personality types or relationships between personality and participation or teaching values, implications of previous studies indicate that there may be concrete differences in the ways that music educators in different teaching settings think about their teaching responsibilities and approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It is also illuminating to consider the variables that were not significant predictors of on-going participation in music. Specifically, demographic variables including age, gender, and personality, which are commonly considered when researching musical behavior, were non-significant predictors, which is itself surprising given the effort that research in music education (e.g., Bowles, 1991;Cutietta & McAllister, 1997;Elpus & Abril, 2011;Kinney, 2010;Torrance & Bugos, 2017;Vaag et al, 2014) has devoted to exploring the impacts of age and gender. While the sample's age range was quite wide, the sample overall was skewed towards younger participants: future research could continue to explore musical participation across the lifespan using quota sampling.…”
Section: Discussionmentioning
confidence: 99%